2012
DOI: 10.1007/s00417-011-1908-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between elevation of serum antinuclear antibody titer and decreased therapeutic efficacy in the treatment of Behçet’s disease with infliximab

Abstract: Background: Infliximab, an anti-TNF- monoclonal antibody, administered to Behçet's disease (BD) patients in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Pink et al have proposed that the development of ANA in psoriatic patients treated with anti‐TNFα may predict treatment failure, but Golberg et al have proposed alternative explanations, as multiple therapies received by these patients could increase the chance of development of ANA [57, 58]. Finally, Iwata et al have showed a correlation between elevated ANA titers and decreased therapeutic efficacy in the treatment of Behçet disease with infliximab [59].…”
Section: Dile Due To Anti‐tnfα Agentsmentioning
confidence: 99%
“…Pink et al have proposed that the development of ANA in psoriatic patients treated with anti‐TNFα may predict treatment failure, but Golberg et al have proposed alternative explanations, as multiple therapies received by these patients could increase the chance of development of ANA [57, 58]. Finally, Iwata et al have showed a correlation between elevated ANA titers and decreased therapeutic efficacy in the treatment of Behçet disease with infliximab [59].…”
Section: Dile Due To Anti‐tnfα Agentsmentioning
confidence: 99%
“…53 Anti-TNFα may lead to apoptotic cell death and the release of autoantigens that induce antiDNA antibodies in susceptible patients. 54,55 Downregulation of TNFα may be associated with autoantibody production due to the upregulation of IL-10, which activates autoreactive B cells. 53 Local complications at the site of drug administration have been frequently reported.…”
Section: Anti-tnfα Agents and Hla-b27-associated Uveitismentioning
confidence: 99%
“…One of the considerations in giving infliximab is that it can potentially induce antinuclear antibody (ANA) and anti-double stranded DNA on long term therapy. [3031] Early monitoring and optimizing dose regimens can be useful in patients on long term Infliximab therapy. It has been shown to be superior to etanercept in preventing relapses and remission in various trials.…”
Section: Biologics In Use For Uveitismentioning
confidence: 99%